Aerodynamic performance evaluation of multi inner blades savonius rotor - Al-Ghriybah, Mohanad (2020)
Savonius wind turbine is the cheapest and simplest type of vertical axis wind turbines. This turbine is being utilized in various countries due to the simplistic design and low construction cost. However, this turbine suffers from low efficiency. For that, this study aims to increase the performance of the Savonius wind rotor in order to generate more useful power. In the present study, the aerodynamics performance of the Savonius wind turbine rotor with inner blades was investigated. The effect of number of inner blades, angle of inner blades, position of inner blades, and distance between the inner blades were evaluated under low and normal ranges of Tip Speed Ratio (TSR) through simulation and experimental work. A numerical investigation was adopted using ANSYS Fluent 19.1 software in order to determine the aerodynamic performance such as power coefficient (Cp) and torque coefficient (Ct). The numerical investigation was performed using two and three-dimensional simulations based on k-Ɛ/realizable turbulence model. Wind tunnel investigation was also carried out for the best-performed Savonius rotor configuration under the various parameters. Both simulation and experimental results were then compared for verification. In general, the results obtained showed that the performance of the Savonius rotor could be significantly improved by the addition of inner blades. The maximum enhancement of Cp was 41% for the case of single inner blade installed at 120o angle and tested at high TSR. As for the double inner blades, a maximum Cp of 13% was achieved when tested at low TSR (installed at 160o angle). The results also indicated that better performance of the Savonius rotor could be obtained when the spacing of inner blade was set at 0.02 m and 0.005 m for single and double inner blades, respectively. However, middle position of inner blades marked better performance for most of the cases. It can conclude that a significant enhancement of Savonius rotor performance can be achieved without high production cost and complex design involved. This solution would be very useful for generating high electricity in rural areas with a low cost